The classification of inequalities: Tests, exams and classes of refugees - Federlein, Katharina; Hondros, Konstantin (Momentum Quarterly, 2019)
From a hermeneutic-sociological perspective, the article examines the extent to which class and classification play a role in dealing with and among refugees. We are interested in whether and how inequalities are effective in this sensitive area, using a broad class concept based on Bourdieu’s conception. Classification is understood as a process that leads to the formation of classes. By comparing bureaucratic-scientific documents, which refers to a political discourse, with participating observations from integration courses, we link distant perspectives in literature. The distinction between ‘self-governing’ and ‘foreign-governing’, laid out in Foucault’s concept of governmentality, allows us to theoretically capture inequalities in dealing with and among refugees themselves. We observe that tests and examinations that determine bureaucratic and scientific discourse are also relevant in self-governing and discover the possibility of subversive self-governing through practices such as celebrating or cheating.